Inclusive Growth toward a Prosperous Asia: Policy Implications - Ifzal Ali; Juzhong Zhuang (Asian Development Bank (ADB), 2007)
Developing Asia is embracing inclusive growth as a key development goal in response to rising inequalities and increasing concern that these could undermine the very sustainability of Asia's growth. This paper argues that inclusive growth emphasizes creation of and equal access to opportunities; and that unequal opportunities arise from social exclusion associated with market, institutional, and policy failures. A development strategy anchored on inclusive growth is outlined, consisting of two mutually reinforcing strategic pillars of high and sustainable growth to create economic opportunities, and social inclusion to ensure equal access to opportunities. This will enable developing Asia to accomplish the agenda of eradicating extreme poverty and, at the same time, address the development challenge brought about by rising inequalities. It is argued that the Asian Development Bank (ADB) should respond to the emerging needs of developing Asia by adopting inclusive growth as its overarching goal. This goal, if adopted, will require ADB to modify its corporate strategy, including its vision, mission, strategic pillars, and core operational priorities. Implications for ADB's country and regional operations are discussed.
hdl:11540/1858
Keywords: 330; Entwicklung; Entwicklungsstrategie; Entwicklungsbank; Asien